2015
DOI: 10.1021/jacs.5b09939
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Metal-Free Catalysts for Selective Soft Oxidative Methane → Ethylene Coupling. Scope and Mechanistic Observations

Abstract: Using abundant soft oxidants, a high methane-to-ethylene conversion might be achievable due to the low thermodynamic driving force for over-oxidation. Here we report on the oxidative coupling of methane by gaseous S2 (SOCM). The catalytic properties of Pd/Fe3O4 are compared with those of Fe3O4, and it is found that high ethylene selectivities can be achieved without noble metals; conversion and selectivity on Fe3O4 are stable for at least 48 h at SOCM conditions. SOCM data for 10 oxides are compared, and ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 84 publications
0
29
1
Order By: Relevance
“…Methane has attracted attention as the main component of natural gas and the conversion of methane into value-added chemicals is very important [ 1 , 2 ]. However, methane is extremely stable, with high C–H bond strengths (439 kJ/mol), negligible electron affinity and low polarizability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methane has attracted attention as the main component of natural gas and the conversion of methane into value-added chemicals is very important [ 1 , 2 ]. However, methane is extremely stable, with high C–H bond strengths (439 kJ/mol), negligible electron affinity and low polarizability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consecutive effort, they further studied the OCM by S 2 (SOCM) over 10 oxides. 73 It was found that the Mg, Zr, Sm, W, and Labased oxide catalysts suffered from severe coking and delivered limited ethylene selectivity, while Fe, Ti, and Cr-based oxide catalysts coked to a minor extent and exhibited much higher selectivity. Notably, the highest ethylene selectivity of 33% was achieved by further optimizing the reaction conditions, which was comparable to that of noble metal catalysts.…”
Section: Oxidative Coupling Of Methanementioning
confidence: 99%
“…By further optimizing the operation conditions, for example, high CH 4 /S ratio, short contact time and the provision of a support, the efficiency of CH x intermediates coupling was significantly promoted with ethylene selectivity approaching 20%. As a consecutive effort, they further studied the OCM by S 2 (SOCM) over 10 oxides 73 . It was found that the Mg, Zr, Sm, W, and La‐based oxide catalysts suffered from severe coking and delivered limited ethylene selectivity, while Fe, Ti, and Cr‐based oxide catalysts coked to a minor extent and exhibited much higher selectivity.…”
Section: Methane Conversionmentioning
confidence: 99%
“…A follow‐up study examined simple metal oxides as catalyst precursors for SOCM [61] . Since the oxides transform into the corresponding metal sulfides following pretreatment in an H 2 S/S 2 mixture, the resulting metal sulfide was considered to be the active phase.…”
Section: S2 As An Oxidant (S2‐ocm)mentioning
confidence: 99%